Iconoclasm from antiquity to modernity: [the majority of the contributors presented papers at a conference on iconoclasm, held at the University of Oslo in 2009 ...] - Kolrud, Kristine (Ashgate, 2014)
Introduction: whose iconoclasm? / Kristine Kolrud and Marina Prusac -- Bursts of destruction: regional variations in iconoclasm in the ancient and late antique world / Eberhard Sauer -- Presence and the image controversies in the third and fourth centuries AD / Marina Prusac -- Defacement and replacement as political strategies in ancient ruler images / Bente Kiilerich -- Byzantine iconoclasm and the belief in eikon Theou: an issue of Christology or a quest for political power? / Anne Karahan -- Neither iconoclasm nor iconodulia: the Carolingian via media / Thomas F.X. Noble -- Iconoclasm and religious images in the early Lutheran tradition / Tarald Rasmussen -- Iconoclasm on the frontier: Le Cateau-Cambrésis, 1566 / Andrew Spicer -- The Waldensians and the Piedmontese Easter of 1655 / Kristine Kolrud -- Iconoclasm: three modern cases / Jens Braarvig -- Conclusion: iconoclasm in history and present-day use of images / Siri Sande